Impact investment in private equity funds. The challenge of achieving social impact and financial returns - Diaz, Gonzalo Javier (2022)
Fil: Diaz, Gonzalo Javier. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.